2014
DOI: 10.1038/nm.3512
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-β superfamily ligand trap ACE-536 corrects anemia by promoting late-stage erythropoiesis

Abstract: Erythropoietin (EPO) stimulates proliferation of early-stage erythrocyte precursors and is widely used for the treatment of chronic anemia. However, several types of EPO-resistant anemia are characterized by defects in late-stage erythropoiesis, which is EPO independent. Here we investigated regulation of erythropoiesis using a ligand-trapping fusion protein (ACE-536) containing the extracellular domain of human activin receptor type IIB (ActRIIB) modified to reduce activin binding. ACE-536, or its mouse versi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
363
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 359 publications
(381 citation statements)
references
References 40 publications
15
363
2
1
Order By: Relevance
“…72 Similarly, a number of recent studies highlight the feasibility of manipulating the TGF-b pathway in hematopoietic disorders like MDS and anemia. 115,118,119 In addition, the complexity of the SMAD pathway continues to be exposed as new layers of regulatory mechanisms are found. For example, the linker region of SMADs is subject to negative regulation by glycogen synthase kinase 3, FGF, and epidermal growth factor.…”
Section: Therapeutic Avenues and Future Perspectivesmentioning
confidence: 99%
“…72 Similarly, a number of recent studies highlight the feasibility of manipulating the TGF-b pathway in hematopoietic disorders like MDS and anemia. 115,118,119 In addition, the complexity of the SMAD pathway continues to be exposed as new layers of regulatory mechanisms are found. For example, the linker region of SMADs is subject to negative regulation by glycogen synthase kinase 3, FGF, and epidermal growth factor.…”
Section: Therapeutic Avenues and Future Perspectivesmentioning
confidence: 99%
“…We tested this idea by treating Bmpr2-floxed and Bmpr2-cKO mice with ACVR2B receptor decoy (ACVR2B-Fc), which sequesters activins with high affinity (Koncarevic et al, 2012;Sako et al, 2010), selectively reduces SMAD2/3 activation (supplementary material Fig. S4A,B; Ohsawa et al, 2006;Suragani et al, 2014;Zhou et al, 2010) and increases bone mass (Attie et al, 2013;Koncarevic et al, 2010). We reasoned that, if the reduced activin signaling underlies high bone mass in Bmpr2-cKO mice, then sequestration of activins with receptor decoy would have little or no additional effect on bone mass.…”
Section: Type 2 Bmp and Activin Receptor Expression In Bone Cellsmentioning
confidence: 99%
“…141 The observation triggered further investigation into this, and another trap ligand targeting ActRIIB (ACE-536), in mouse models of myelodysplastic syndromes (MDS) as well as b-thalassemia, showed a significant improvement of the anemia. [142][143][144] In both these disorders it has been suggested that the mechanism of action of these drugs is mediated by targeting Gdf11, which in turn decreases Smad2/3 activation in erythroid progenitors, and ultimately improves erythroid maturation and RBC production. [142][143][144] In addition, in Hbb th1/th1 mice, it has been shown that oxidative stress, through the Gdf11 ligand (Figure 3), also decreases apoptosis through overactivation of the Fas-Fas ligand pathway.…”
mentioning
confidence: 99%
“…[142][143][144] In both these disorders it has been suggested that the mechanism of action of these drugs is mediated by targeting Gdf11, which in turn decreases Smad2/3 activation in erythroid progenitors, and ultimately improves erythroid maturation and RBC production. [142][143][144] In addition, in Hbb th1/th1 mice, it has been shown that oxidative stress, through the Gdf11 ligand (Figure 3), also decreases apoptosis through overactivation of the Fas-Fas ligand pathway. 126,127 As mentioned previously, both decreased apoptotic rate and maturation of early erythroid precursors leads to exacerbation of IE, splenomegaly, and increased iron absorption.…”
mentioning
confidence: 99%